Rural Community Engagement for Heritage Conservation and Adaptive Renewal - Glenn C. Sutter; Leah O'Malley; Tobias Sperlich (The University of Alabama, 2023)
Systems thinking can shed light on important relationships and conditions that affect community engagement activities. While robust tools like the community capitals framework and the sustainable livelihoods approach provide valuable context for engagement projects, additional insights can stem from models that describe the ebb and flow of different types of capital. This paper uses a well-studied ecosystem model called adaptive renewal (AR) to contextualize heritage-related challenges and opportunities in four rural communities on the Canadian prairies. Based on a reflective case-study analysis, we applied the AR model to focus group and semistructured interview data collected as part of a Museums Association of Saskatchewan (MAS) project aimed at using local heritage assets to build sociocultural and environmental capacity and attract investment. The MAS project identified four themes that could be addressed through training and policy changes, including concerns about funding, limited human resources, a lack of public services, and a desire to preserve and build on memories. By mapping each community onto the AR model, we uncovered additional insights about community resilience and other heritage-related challenges and opportunities. The AR model is likely to be a valuable tool for planning or assessing community engagement projects because it reflects the dynamic nature of socioeconomic and cultural relationships that affect community dynamics and local well-being.